Evaluation of the Rationality of Antituberculosis Drug Use in Pulmonary Tuberculosis Patients at Jaury Jusuf Putra Academic Hospital in 2024 (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Background: Infectious diseases are illnesses caused by microorganisms such as viruses, bacteria, fungi, or parasites that can spread from one person to another. Tuberculosis (TB), caused by Mycobacterium tuberculosis, is a contagious disease primarily targeting the lungs but also capable of affecting other organs, including the skin, lymph nodes, bones, and meninges. The rational use of medication plays a vital role in ensuring the success of TB treatment and preventing the emergence of drug resistance. Objective: This study aimed to assess the rationality of antituberculosis drug administration, focusing on four key criteria—right patient, right indication, right drug, and right dose—based on established TB treatment guidelines. Methods: A non-experimental, observational descriptive design with retrospective data collection was applied. Data were obtained through purposive sampling from the medical records of pulmonary TB patients treated at Jaury Jusuf Putra Academic Hospital. The sample size, calculated using the Slovin formula, included 87 patients out of a total of 690 recorded between January and December 2024. Results: The findings indicated that the appropriateness of patient selection met the standard in 100% of cases. However, indication appropriateness and drug appropriateness were each achieved in only 66% of cases, while dose appropriateness was markedly lower at 49%. Most patients (64%) received Category I therapy with the HRZE regimen. Males accounted for 66% of the sample, and the age group with the highest prevalence was 56–65 years (26%). Conclusion: Although patient targeting was fully in accordance with guidelines, shortcomings remain in indication, drug selection, and especially dosing. These results underscore the importance of reinforcing compliance with TB treatment protocols and improving clinical judgment in prescribing practices.